Proceedings of the second international symposium on lychee, longan, rambutan, and other sapindaceae plants (poster session) (Horticultural Science Society of Thailand, 2005)
List of content: genetic resources and breeding; Biotechnology; Cultural practices and physiology: nutrient, nitrogent, carbohyrate, NPK...; Plant protection.